A cross-sectional questionnaire-based study of medication adherence in children suffering from epilepsy attending pediatric out-patient department at a tertiary care teaching hospital - Joshi, Khilen P.; Bhave, Amol L.; Vyas, Pratit P. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Epilepsy is a common chronic disease presenting during childhood that requires long-term treatment. Rates of adherence to antiepileptic drugs are variable in children ranging from 25% to 75%. Non-adherent patients are more likely to experience frequent and recurrent seizures which drastically impact the health of the patient. This study was therefore conducted in order to assess the medication adherence of children suffering from epilepsy to the prescribed anti-epileptic drug therapy. Methods: Children diagnosed with epilepsy aged 6-18 years were enrolled in the present cross-sectional questionnaire-based study after prior written informed consent and written informed assent. Children with co-morbidities were excluded from the study (as diagnosed by the Paediatrician). The case record form was filled after interviewing the patients. A questionnaire based on the Morisky medication adherence scale-8 (MMAS) was used to evaluate the quality of life of children. Results: Total 243 patients got enrolled in the study. GTCS was found to be the most common type of epilepsy. Valproate was the most commonly used agent. Out of the 243 patients in total, 201 patients (83%) showed high adherence, 24 patients (10%) showed medium adherence and 18 patients (7%) showed poor adherence to the treatment prescribed. Patients on monotherapy showed higher adherence rates than patients on polytherapy. Medication adherence was highest with Valproate among monotherapy and valproate + carbamazepine among poly-therapy. Conclusions: We conclude that monotherapy with anti-epileptic agents and patient satisfaction is positive predictors of medication adherence leading to a lesser impact of the disease on the child and improved health.